Hubungan Antara Self Efficacy Dan Social Support Dengan Tingkat Stres Pada Mahasiswa Akhir Penyusun Skripsi Di FIP UNNES Tahun 2019 - Saputri, Kiki Anggun; Sugiharto, DYP (IAIN Kudus, 2020)
The Relationship Between Self Efficacy and Social Support With the Level of Stress in Final Thesis Compilers in FIP UNNES. The Study aims to determine the relationship between self efficacy and social support with stress levels in the final student of the thesis at the FIP unnes in 2019. The underlying problem of this research is the occurrence of several phenomena in FIP UNNES. These phenomena relate to the level of stress composing thesis. Many students are stressedbecause of difficulties in determining the title of the thesis, the lecturer is busy, the difficulty of finding relevant sources and the lack of support fromothers. The methods used in this study is a quantitative methods that uses two data collection tools namely the picological scale and interview techniques. The result of this study are that there is a significant relationship between self efficacy and social support with stress levels. The results of this study are also beneficial for the department and the faculty in drafting academic policies as well as other advocates that can suppress the rate of stress and improve self efficacy and social support studentsKeywords: Stress Level; Self Efficacy; Social Support